1999
DOI: 10.1002/chin.199921280
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Coupling of Organic Halides with Carbonyl Compounds Promoted by SmI2, the Kagan Reagent

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In particular, reductive ET to organic compounds is a powerful method for the activation of substrates via the formation of radicals, radical anions, anions, and dianions that can be exploited in bond-cleaving and bond-forming reactions. While alkali metals were used in early synthetic ET procedures, the latter half of the 20th century saw the emergence of a new generation of reductive ET reagents. At the vanguard of this new order was samarium diiodide (SmI 2 ), and the incredible synthetic potential of this reagent was quickly recognized and mapped by the leading synthetic teams of the day. Indeed, since its introduction to the synthetic community in 1977 by Kagan, , SmI 2 has become one of the most important reducing agents available in the laboratory. , In his seminal paper, Kagan observed that “carboxylic acid and ester were not reduced by SmI 2 ”, and this view became widely accepted in the field . It has taken over 35 years to overturn this dogma and for the reduction of carboxylic acid derivatives using SmI 2 to take its place alongside aldehyde/ketone reduction as a powerful activation mode for synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, reductive ET to organic compounds is a powerful method for the activation of substrates via the formation of radicals, radical anions, anions, and dianions that can be exploited in bond-cleaving and bond-forming reactions. While alkali metals were used in early synthetic ET procedures, the latter half of the 20th century saw the emergence of a new generation of reductive ET reagents. At the vanguard of this new order was samarium diiodide (SmI 2 ), and the incredible synthetic potential of this reagent was quickly recognized and mapped by the leading synthetic teams of the day. Indeed, since its introduction to the synthetic community in 1977 by Kagan, , SmI 2 has become one of the most important reducing agents available in the laboratory. , In his seminal paper, Kagan observed that “carboxylic acid and ester were not reduced by SmI 2 ”, and this view became widely accepted in the field . It has taken over 35 years to overturn this dogma and for the reduction of carboxylic acid derivatives using SmI 2 to take its place alongside aldehyde/ketone reduction as a powerful activation mode for synthesis.…”
Section: Introductionmentioning
confidence: 99%